Teachers’ Connectedness to Nature, Education for Sustainable Development and the Contemporary Teaching of the Subject “Nature and Society” in Croatian Schools - Anđić, Dunja; Mažar, Sandra (Journal of Teacher Education for Sustainability, 2023)
The modern approach to teaching in schools is based on encouraging pupils’ activity in learning about the natural and social phenomena; the pupil is an active participant in the teaching process. The “Nature and Society” subject curriculum emphasizes the use of ICT technologies and various teaching methods. The teacher, their practice, emotions, personality, and competencies play an important role in achieving the learning outcomes in school subjects, as well as in cross-curricular topics, such as is the Sustainable Development Curriculum. This paper presents a study that examined teachers’ Love and Care for nature as an important component of promotion of ESD and the practice of using modern approaches in teaching of the subject “Nature and Society”. The results of the study show that there is a statistically significant relationship between teachers’ Love and Care for nature and modern approaches to learning and teaching the subject “Nature and Society” and the implementation of ESD in primary schools in Croatia.